Alumni Club of Washington, D.C. - Frank R. Hupp, Strasburg, VA (Z. Smith Reynolds Library, 2008)
ca. 1950
alumni at picnic, July 12
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth